ARTEFAK LITIK CERUK LAYAH, SAMPUNG : KAJIAN TEKNOEKONOMI - Indah Asikin Nurani (Berkala Arkeologi, 2003)
Lawa Cave's multi-functional activities include food processing activities as evidenced by the findings of ecofacts (food scraps in the form of bone fragments and mollusc shells), tool-making activities (workshops) with evidence of the findings of artifacts including tools, waste and raw materials, and graves human skeleton findings). Meanwhile, the single activity in the Layah rockshelters was evidenced by findings that were dominated by lithic artifacts, including in the form of debitage, tool products, raw materials and core stones. The Lawa Cave which has a large area and is located near the river is used as a place for multi-functional activities, while the Layah Caves where the surrounding area is a source of raw materials is used as a place for making lithic tools. Based on the differences in activities and the quality of these raw materials in dealing with and adapting to the surrounding natural environment, it shows that there is a distinct character in the settlement patterns that take place in this area. Furthermore, based on technological observations and typology of the Layah rockshelter, it shows that humans at that time were exploiting nature optimally.